10-GHz Optical Comb in L-Band Region With Brillouin/Erbium-Doped Fibre Laser - Harun, Sulaiman Wadi; Tamchek, Nizam; Abd-Rahman, Mohd Kamil; Poopalan, Prabakaran; Ahmad, Harith (Springer Verlag (Germany), 2003)
A multiwavelength Brillouin / erbium fibre laser (BEFL) which operates in the long wavelength (L-band) region is demonstrated for potential applications in an L-band wavelength division multiplexing (WDM) communication system. The laser configuration consists of a long erbium-doped fibre to enable L-band amplification where two 3-dB couplers take a portion of the generated BEFL signal and re-inject it into the single mode fibre to seed a cascaded BEFL line in the same direction as the first BEFL line. A stable and strong laser comb of up to five lines with 10-GHz spacing has been obtained with a Brillouin pump (BP) of 9.2 mW and a 980 nm pump of 92 mW. The BEFL has shown a broad tuning range with a tuning characteristic for line #1 which is flat over a range greater than 9.9 nm.